The impact of engaging with community groups: asset-based approaches and the lived experience of socially vulnerable populations in the UK - Corrigan, Oonagh; Hughes, Suzanne; Danielsen, Scott; Doherty, Shannon; Kabir, Russell (Frontiers in Public Health, 2023)
In this paper we report on two sequential research studies carried out between 2019 and 2021 in the East of England. This work provides a contextual understanding of the relationship between wellbeing, place, and communities in the context of prevailing health and social inequalities. With a focus on vulnerable populations and a diverse range of community groups, we present narrative accounts of the perceived wellbeing benefits experienced by members because of their participation in a community group forum. Findings illustrate the central role these groups play in creating and maintaining wellbeing, through reducing social isolation and strengthening resilience among some of the region’s most vulnerable populations. They do so by providing physical and/or other activities of shared interest, forums for listening and sharing with other members, and imparting information that supports members’ wellbeing. Wellbeing benefits were evidenced in the initial study which was carried out before national COVID -19 restrictions were introduced in March 2020. However, the importance of such groups was further highlighted in findings from the subsequent study which focussed on experiences of group members when COVID -19 restrictions were in place and social gatherings were greatly curtailed. The studies’ findings support the supposition that these groups are community assets which help ameliorate against the social detriments of health and wellbeing that have led to widening health inequalities in the region. This paper will reflect further on the implications of this research for local and national government initiatives to address rising inequalities and the promotion of community wellbeing and health promotion initiatives.